Occupy until I come A.T. Pierson and the evangelism of the world - Robert, Dana Lee (Grand Rapids, MI Eerdmans, 2003)
Includes bibliographical references and index.
Keywords: Pierson, Arthur Tappan, -- 1837-1911; Presbyterian church -- United States -- clergy -- biography; Evangelistic work -- United States -- history; Missions, American -- history